Impact behaviour of spherical-roof contoured-core (SRCC) sandwich panel under the low-velocity impact (LVI) : A numerical investigation - Quanjin, Ma; Mohd Ruzaimi, Mat Rejab; Shukur, Hj Abu Hassan; Hu, Haichao; Mohammad, Azeem; Yunus Nasution, Ahmad (Elsevier Ltd, 2023)
Sandwich panels are multifunctional composite structures with two stiffer skin sheets and core, which have better mechanical properties than traditional structures. It is challenging to improve the energy-absorption characteristics and impact resistance while maintaining the required mechanical performance under quasi-static and dynamic loadings. Various core designs of sandwich structures have been studied on the failure mechanism under dynamic loading. This paper was investigated the impact behaviour of sandwich panels with spherical-roof contoured core (SRCC) design under low-velocity impact (LVI) loading impact loading, which is used in finite element modelling. The core structure and two skin sheets were used carbon fibre-reinforced plastic (CFRP). It was used the cohesive element to predict the adhesive interface between the skin sheet and the spherical-roof core. The three-dimensional (3D) Hashin failure criterion was implemented to predict the impact behaviour. The single-peak load curve on the load versus displacement curve was observed on type 1 with 5.71 kN, and the double-peak load curve was found on type 2 with 7.12 kN. Furthermore, it was calculated that the internal energy of the SRCC sandwich panel was 51.67 J with type 2, which was 1.81 times higher than type 1.